A Role for Barley Calcium-Dependent Protein Kinase CPK2a in the Response to Drought - Cieśla, Agata; Mituła, Filip; Misztal, Lucyna; Fedorowicz-Strońska, Olga; Janicka, Sabina; Tajdel-Zielińska, Małgorzata; Marczak, Małgorzata; Janicki, Maciej; Ludwików, Agnieszka; Sadowski, Jan (Frontiers in Plant Science, 2016)
Increasing the drought tolerance of crops is one of the most challenging goals in plant breeding. To improve crop productivity during periods of water deficit, it is essential to understand the complex regulatory pathways that adapt plant metabolism to environmental conditions. Among various plant hormones and second messengers, calcium ions are known to be involved in drought stress perception and signaling. Plants have developed specific calcium-dependent protein kinases that convert calcium signals into phosphorylation events. In this study we attempted to elucidate the role of a calcium-dependent protein kinase in the drought stress response of barley (Hordeum vulgare L.), one of the most economically important crops worldwide. The ongoing barley genome project has provided useful information about genes potentially involved in the drought stress response, but information on the role of calcium-dependent kinases is still limited. We found that the gene encoding the calcium-dependent protein kinase HvCPK2a was significantly upregulated in response to drought. To better understand the role of HvCPK2a in drought stress signaling, we generated transgenic Arabidopsis plants that overexpressed the corresponding coding sequence. Overexpressing lines displayed drought sensitivity, reduced nitrogen balance index (NBI), an increase in total chlorophyll content and decreased relative water content. In addition, in vitro kinase assay experiments combined with mass spectrometry allowed HvCPK2a autophosphorylation sites to be identified. Our results suggest that HvCPK2a is a dual-specificity calcium-dependent protein kinase that functions as a negative regulator of the drought stress response in barley.